A bibliometric and topic analysis of climate justice: Mapping trends, voices, and the way forward - Meg Parsons; Quinn Asena; Danielle Johnson; Johanna Nalau (Climate Risk Management, 2024)
The field of climate justice has been growing in relevance since its conception in 1997. This paper presents a comprehensive bibliometric and topic modelling analyses to examine the evolution and trajectory of the climate justice literature. We analyse 1,683 publications covering the period from 1997 to 2021, highlighting foundational works, influential authors, leading nations and institutions, and prevailing research topics within this field. We employ Latent Dirichlet Allocation to uncover latent research trends in the literature providing a crucial baseline for future scholarly endeavours and policy development in the realm of climate justice.Our results show that the field of climate justice has grown exponentially from less than 5 papers annually between 1997 and 2005, to around 200 papers annually in recent years. This growth has seen a diversification of research themes with an increase in papers around the topics of health, vulnerability and adaptation, and policy and activism. There has been a consistent backdrop of publications around the topics of sustainable development and policy, and international relations and carbon emissions. Other prominent topics in the literature include education and food security, and human rights and Indigenous people. The field has moved from theoretical research to examining actual examples of climate injustices, with an increased diversification of topics.Future research could usefully focus on exploring future generations and more-than-human entities; the integration of climate justice and climate activism with broader struggles for justice; re-thinking climate adaptation “success” and “effectiveness” through the lens of climate justice, and the ramifications of the Global Goal on Adaptation on climate justice led-approaches that are inclusive, build on human rights approaches, and extend the scale of adaptation analysis beyond the local. It is imperative to prioritise addressing the climate justice needs of those most affected by climate change, transcending national borders, generational gaps, cultural differences, and even the well-being of various species. Such a holistic approach will help inform and refine global climate policy and action.